Testing Real Interest Parity in Emerging Markets - Banerjee, Abhisek (IMF Working Papers; Working Paper ;, 2006)
The paper finds significant deviations between short-term emerging market real interest rates and world real interest rates primarily due to the inflationary expectations of the local investor base. We test for long-run real interest convergence in emerging markets using a time varying panel unit root test proposed by Pesaran to capture the improved macro-economic fundamentals since early 1990s. We also estimate the speed of convergence in the presence of a shock. The paper suggests that real interest rates in the emerging markets show some convergence in the long run but real interest parity does not hold. Our results also find that the speed of adjustment of real rates to a shock is estimated to differ significantly across the emerging markets. Measured by their half-life, some emerging markets in Asia, E.Europe and S.Africa, where real interest rates are generally low, take much longer to adjust than where real interest rates are generally high (Latin America, Turkey). From a policy perspective, encouraging foreign investors to take direct exposure at the short end of the local debt market could lower the real interest rates in some emerging markets.